Visual Communication Design for Online Promotion via Facebookat CV. Cahaya Grafika in Demak (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
This study aims to develop and evaluate a VisualCommunication Design (VCD) strategy for onlinepromotion through Facebook at CV. Cahaya Grafikain Demak. The research applied a design-basedapproach, combined with audience perception testingusing a Likert-scale questionnaire distributed to 30respondents aged 18–44 years. The developmentproduced five main outputs: Facebook photo posts,profile and cover design, group posts, story-formatcontent, and adaptation for printed banner media. Theresults show significant improvement in visualattractiveness, message clarity, brand recognition,and engagement performance. The findings indicatethat systematic visual optimization enhancespromotional effectiveness in both digital and printmedia.